Successful outcome of a severe COVID-19 patient with multiple co-morbidities: a case report (BIRDEM Medical Journal, 2020)
Patients with severe form of corona virus disease 2019 (COVID-19) with multiple co-morbidities can be treated successfully. We report a case of COVID-19 pneumonia complicated by acute respiratory distress syndrome (ARDS), occurring in an elderly male patient with (co-morbid )diabetes mellitus, hypertension, chronic kidney disease and obstructive sleep apnea. This case is reported to emphasize that managing severe COVID-19 patient with multi-disciplinary approach, keeping in mind each of the co-morbidities, can result a fourable outcome.Birdem Med J 2020; 10, COVID Supplement: 127-130